A study of Radio Zimbabwe's messages and audiences in a time of crisis - Mudavanhu, Selina Linda (Centre for Film and Media Studies, 2015)
The political and economic crisis that beset Zimbabwe since the late 1990s forms the backdrop to this study which examines the discourses that occupied a position of dominance on the state radio station, Radio Zimbabwe, between March and April 2011. This study moves beyond an analysis of texts and also looks at how some women listeners, who were living in a rural community in Zimbabwe, engaged with the radio and the mainstream discourses in the context of everyday life. The analysis of Radio Zimbabwe broadcasts is informed by Antonio Gramsci's concept of hegemony (1971) as well as ideas from the propaganda model postulated by Edward Herman and Noam Chomsky (1988). The audience study draws on some ideas by Carragee (1990) on the critical audience research perspective. This study also takes a poststructuralist approach to language, discourse and subjectivity. Available media scholarship on the post-2000 crisis in Zimbabwe has mostly focused on analysing how the print media represented the land question and the elections. Scholars have neglected to look at hegemonic and counter hegemonic discourses that were broadcast on the most pervasive medium in the country and on the continent, radio during this time. In radio studies in Africa and in Zimbabwe, the exploration of radio content is also largely missing. Also conspicuously absent in research that has been carried out in Zimbabwe and in Africa is an understanding of how audiences interact with mainstream meanings embedded in radio texts. In view of the above-mentioned gaps in literature, this study focuses on radio texts and radio listeners. The study combines a critical discourse analysis of Radio Zimbabwe content with a discourse analysis of narratives of 30 women listeners of the station that were interviewed. Two arguments are made in this thesis. The first is that in the face of waning support, immense opposition at home and abroad and an unrelenting economic crisis, the Zimbabwe African Nationalist Union- Patriotic Front (ZANU-PF) government used the discourses on land, the liberation struggle, the father of the nation, Christianity and God to legitimise its continued stay in power. These discourses were also used to delegitimise political opponents inside and outside the country. The second argument that this thesis makes is that women's engagement with Radio Zimbabwe content and hegemonic meanings broadcast on the station is not straightforward and predictable. Though some women said they listened to the news, a programme embedded with dominant ideas, most of them said they did not remember what was contained in most bulletins. Most women recalled news items that were directly relevant to them. While Radio Zimbabwe content was predominantly political in nature, the programmes that women talked about as favourite programmes had nothing to do with politics. The majority of women in the study singled out Kwaziso/Ukhubingelelana and Chakafukidza Dzimba Matenga as programmes they enjoyed listening to. In terms of interacting with mainstream ideas, most of the time many of the women affirmed the dominant discourses. There were, however, instances when some women contested hegemonic ideas. Sometimes mainstream ideas were challenged because what the women heard on the radio and their lived realities were not congruent. Interestingly, there were also times when this disjuncture did not drive women to question what they heard on the station.